PEMBERDAYAAN KELOMPOK TANI IKAN PADA BUDIDAYA IKAN AIR TAWAR DI UNIT TANJUNG BIDARA KAMPONG GAJAH MALAYSIA - Ashari, Riza; Isnatin, Umi; Trisnaningrum, Niken; Wawa, Laola Badu; Herlangga, Muhammad; Parwi, Parwi (UNIVERSITAS PGRI MADIUN, 2025)
Abstract. The natural resources owned by rural communities are the potency that need to be developed in order to increase the economy. The freshwater fish farming group in the Tanjung Bidara Unit, Kampong Gajah, Malaysia, is the regional economy activator. The potential for developing freshwater fish is quite extensive, by taking advantage of river flows. The aim of this community service activity was to improve the economy of the Gajah village area through empowering fish farming groups. The methods that have been implemented are freshwater fish cultivation and marketing education. As the results, the education given increase in fish farmers' knowledge by 75%, including the knowledge of cultivating good freshwater fish and marketing of the products. The conclusion from this activity was that the community's economy can be improved through empowering freshwater fish farmers. Abstrak. Sumber Daya alam yang dimiliki masyarakat pedesaan merupakan potensi yang ada untuk dikembangkan guna meningkatkan perekonomian masyarakat desa Kelompok tani ikan air tawar di Unit Tanjung Bidara Kampong Gajah Malaysia merupakan penggerak perekonomian daerah tersebut. Potensi pengembangan ikan air tawar cukup luas, dengan memanfatakan aliran sungai. Tujuan kegiatan pengabdian ini untuk meningkatkan perekonomian daerah kampong Gajah melaui pemberdayaan kelompok tani ikan. Metode yang telah dilaksanakan adalah penyuluhan budidaya ikan air tawar dan pemasaran. Hasil kegiatan pengabdian masyarakat berupa peningkatan pengetahuan petani ikan sebesar 75% mengenai budidaya ikan tawar yang baik dan pemasaran hasil ikan. Kesimpulan dari kegiatan pengabdian masyarakat ini adalah perekonomian masyarakat dapat ditingkatkan melalui pemberdayaan petani ikan air tawar.